2010
DOI: 10.3109/10641960902993103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prehypertension on Arterial Stiffness and Wave Reflections

Abstract: The Seventh Report of the Joint National Committee on the Prevention, Detection, Evaluation, and Treatment of High Blood Pressure classifies blood pressure (BP) as normal, prehypertension, and hypertension. Although it has been shown that there is a relationship between hypertension and arterial stiffness, there is not sufficient data about arterial stiffness in patients with prehypertension. The present study was designed to evaluate arterial stiffness and wave reflections in subjects with prehypertension. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 25 publications
2
29
1
2
Order By: Relevance
“…These findings are consistent with previous studies that reported an association between PWV and prehypertension (24). Blacher et al showed an association between PWV and the development of cardiovascular disease or cardiovascular death (5, 25).…”
Section: Discussionsupporting
confidence: 94%
“…These findings are consistent with previous studies that reported an association between PWV and prehypertension (24). Blacher et al showed an association between PWV and the development of cardiovascular disease or cardiovascular death (5, 25).…”
Section: Discussionsupporting
confidence: 94%
“…As shown in Table 5, our result indicates that arterial stiffness is heavily dependent on age, SBP, and heart rate in even nonhypertensive individuals. Our subgroup analyses showed that prehypertension itself is not only a risk for both increased arterial stiffness and microalbuminuria, consistent with the previous studies [1,33]. Moreover, the association between baPWV and microalbuminuria is stronger in prehypertensive than in normotensive individuals (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…24 These elevated BP trends would be expected in the setting of significant vascular stiffness, as prehypertensive adults display both impaired arterial functions and elevated PWV. 25 The observed elevation in PWVcf without elevation of pulse pressure in this cohort may be related to overestimation of diastolic pressure by the automated cuff, altered volume status and heart rate in fasting patients, or indicate disproportionate changes in the aorta compared to the peripheral arteries. Characteristics of large versus small vessel disease and their relative contribution to pulse pressure and systemic vascular resistance will be important in understanding the basis for the marked abnormalities observed in PWVcf.…”
Section: Discussionmentioning
confidence: 72%